Determination of Parameter Sensitivity Maps of Surface Linear Geoelectric Arrays - S. Szalai; L. Szarka; M. K. Baracza; P. Szucs (Current Advances in Geography, Environment and Earth Sciences Vol. 4, 2022)
Parameter sensitivity maps of surface linear geoeletric arrays and their practical use are illustrated in this paper. Parameter sensitivity maps are defined as geoelectric responses in the measuring plane (at the surface) due to an elementary cube within the subsurface at three different depths. Electrical dipoles produced on opposite cube surfaces have three component and total responses, which are depicted. These maps are shown in this work for 14 different linear electrode arrays. This chapter is followed by an accompanying one about nonlinear and focussed arrays. In these two chapters, parameter sensitivity maps are used to characterize all known geoelectric arrays. We show how to use them in the planning and interpretation of field measurements with various examples.